The structure of the brain and human behaviour - Wróbel, Grzegorz (Journal of Education, Health and Sport, 2018)
Currently, the state of knowing the structure and functionality of the human brain is a source of interest for many researchers. Despite the fact that there are significant advances in neurobiology, there is still a lack of information on neuroanatomy and neurophysiology that could shed a new look at interpersonal behavior. Changes in the structure of the human brain, which may occur as a result of various factors, affect its functioning and thus human behavior. In the context of neuroanatomic and metabolic changes, cognitive functioning, as well as the expression and control of emotions are also modified. It is worth noting that during the adolescence period, the human nervous system is particularly sensitive to injuries, and dysfunctions of the brain structures that can interfere with for overly risky or even aggressive behavior. The aim of this work was to determine the basic anatomical structures in the functional aspect conditioning human behavior.